IgM deposition is a risk factor for delayed remission and early relapse of the pediatric minimal change disease - Ju, Tao; Peng, Yingchao; Wei, Yaqin; Li, Xiaojie; Wang, Meiqiu; Wang, Ren; Yang, Xiao; Zhang, Zhiqiang; Gao, Chunlin; Xia, Zhengkun (Frontiers in Pediatrics, 2023)
Background: Minimal change disease (MCD) is the most common pathological subtype of pediatric idiopathic nephrotic syndrome (INS). It has been suggested that IgM deposition might predict kidney function deterioration in the course of MCD. However, the specific role of IgM deposition in the prognosis of MCD is still controversial. This study aims to investigate the clinical significance of IgM deposition on delayed remission and early relapse in a pediatric population. Methods: This study enrolled 283 children diagnosed with MCD by renal biopsy in a single center from 2010 to 2022. These cases were divided into two groups according to the histopathological deposition of IgM. Patients' demographics, clinical parameters, and follow-up data were collected and analyzed. The primary and secondary outcomes were defined as the time to the first remission and the first relapse. Results: The IgM-positive group had a weaker response to steroids (steroid-sensitive: 23.5% VS 40.8%; steroid-dependent: 74.0% VS 51.0%；steroid-resistant: 18.4% VS 8.2%, P=0.001), and showed more recurrent cases (47.2% VS 34.4%, P=0.047) compared with the IgM-negative group. The Kaplan-Meier analysis showed that the IgM-positive group had a lower cumulative rate of the first remission (Log-rank, P＜0.001) and a higher rate of the first relapse (Log-rank, P=0.034) than the IgM-negative group. Multivariate Cox analysis showed that IgM deposition was independently associated with the delayed first remission (hazard ratio [HR]=0.604, 95% confidence interval [CI]=0.465-0.785, P<0.001) and the early first relapse (HR=1.593, 95% CI=1.033-2.456, P=0.035). Conclusions: IgM deposition was associated with a weaker steroid response. MCD children with IgM deposition were prone to delayed first remission and early first relapse.